FAKTOR YANG MEMENGARUHI CASH HOLDING DENGAN GOODWILL SEBAGAI VARIABEL MODERASI - Anggraini, Ellen; Imelda, Elsa (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to examine the relationship between firm size, leverage, and profitability on cash holding moderated by goodwill in non-financial services companies listed on the Indonesia Stock Exchange (IDX) during 2018-2020. This sample for this study was selected using purposive sampling method. The total sample obtained is 690 samples. Hypothesis testing is carried out after performing classical assumption, using the panel data analysis method. This study was processed using the EViews 12 student lite version. The results of this study indicate that COVID-19 and firm size have no significant effect on cash holding, profitability has positive significant effect, meanwhile leverage has negative significant effect on cash holding, and goodwill can strengthen the effect of COVID-19 on cash holding. Management may also consider recognizing goodwill when acquiring a company, because the goodwill can strengthen the company's ability to increase cash holding during economic uncertainties, such as what happened during the COVID-19 pandemic.